SOME PATHOGENETIC, CLINICAL AND THERAPEUTIC ASPECTS OF OSTEOPOROSIS IN CHILDREN - I.M. Vazhnova; A.G. Il'in; U.N. Klochkova (Педиатрическая фармакология)
Paper is devoted to violations of bone mineral density, in particular to osteoporosis. The authors emphasize the importance of the disease, stating that it is included in the list of 5 the most important human diseases. Markers of bone formation and resorption,  a number of electrolytes and trace elements involved in the metabolism of bone tissue are represented. The article describes the basic mechanisms of formation, clinical, diagnostic and therapeutic aspects of osteoporosis in children. The authors describe the bone lesion in juvenile osteoporosis and rare hereditary syndromes. The principles of osteoporosis therapy in children are covered. Key words: bone mineral density, bone quality, osteoporosis, juvenile osteoporosis, osteogenesis markers, markers of bone resorption, bone metabolism, treatment, children. (Pediatric pharmacology. — 2011; 8 (6): 30–35).